(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
In the writing resonates the great question that haunts us as Anthropologists, so our contribution will always be to assume the challenge of understanding the unifying laws, insisting on divergences and kinship. It is ours, the tradition of the study of society immersed in a culture and its historical evolution. So the proposal is to visualize: the virtue of humanism and the error of disconnection with reality (epistemic obstacle). This In Therefore, the learnings of the Bicentennial are a path with obligatory passage to admire its academic landscape: with theoretical volcanoes and lakes full of methodological approaches. That is what this invitation is about, to dare to think about the real, ideal and symbolic.